THE EFFECT OF BUILDING FAÇADE MODEL ON LIGHT DISTRIBUTION (CASE STUDY: MENARA PHINISI BUILDING OF UNM) - Jamala, Nurul (DIMENSI (Journal of Architecture and Built Environment), 2017)
Global warming issues influence the temperature of the earth surface. It is an impact on energy consumption, especially in buildings. Utilization of daylight is one of the factors that need to be considered, in order to minimize energy consumption as a source of artificial lighting. This study analyzed the distribution of light on the Menara Phinisi building of Makassar State University. Quantitative research method that is to describe the data of simulation in Autodesk Ecotect program. The research objective was to determine the effect of the building facade model on the value of illumination inside the building. Results of the study concluded that the decrease percentage of the distribution of light on the building facade using and not using the facade is 3,16% or 236 lux. Distribution of light in horizontal and diagonal facade models differ in the amount of 2,5%. Design analysis of the building serves as a guide for analyzing the influence of the building facade model so that it can create energy efficient buildings.